Praf2 is a novel Bcl-xL/Bcl-2 interacting protein with the ability to modulate survival of cancer cells. - Maria Teresa Vento; Valeria Zazzu; Alessia Loffreda; Justin R Cross; Julian Downward; Maria Patrizia Stoppelli; Ingram Iaccarino (PLoS ONE)
Increased expression of Bcl-xL in cancer has been shown to confer resistance to a broad range of apoptotic stimuli and to modulate a number of other aspects of cellular physiology, including energy metabolism, cell cycle, autophagy, mitochondrial fission/fusion and cellular adhesion. However, only few of these activities have a mechanistic explanation. Here we used Tandem Affinity purification to identify novel Bcl-xL interacting proteins that could explain the pleiotropic effects of Bcl-xL overexpression. Among the several proteins co-purifying with Bcl-xL, we focused on Praf2, a protein with a predicted role in trafficking. The interaction of Praf2 with Bcl-xL was found to be dependent on the transmembrane domain of Bcl-xL. We found that Bcl-2 also interacts with Praf2 and that Bcl-xL and Bcl-2 can interact also with Arl6IP5, an homologue of Praf2. Interestingly, overexpression of Praf2 results in the translocation of Bax to mitochondria and the induction of apoptotic cell death. Praf2 dependent cell death is prevented by the co-transfection of Bcl-xL but not by its transmembrane domain deleted mutant. Accordingly, knock-down of Praf2 increases clonogenicity of U2OS cells following etoposide treatment by reducing cell death. In conclusion a screen for Bcl-xL-interacting membrane proteins let us identify a novel proapoptotic protein whose activity is strongly counteracted exclusively by membrane targeted Bcl-xL.